1995
DOI: 10.1002/mds.870100416
|View full text |Cite
|
Sign up to set email alerts
|

Cervical dystonia due to spinal cord ependymoma: Involvement of cervical cord segments in the pathogenesis of dystonia

Abstract: We report a patient with a progressive motor disorder dominated by pyramidal signs in all four extremities and cervical dystonia in the form of torticollis, who had imaging features of cervical cord tumor on magnetic resonance imaging (MRI) scanning. Ependymoma was the final diagnosis by histology. Cervical dystonia presenting as a manifestation of an identified focal central nervous system (CNS) lesion is infrequent. We believe our patient to be the first adult example of cervical cord tumor giving rise to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…The authors found that the corticospinal tracts demonstrated dysfunction in all patients, while SSEPs remained normal [8] . The theory of corticospinal tract dysfunction or other long tract dysfunction, such a spinothalamic tract, is further supported by the case reports on cervical intramedullary tumors presenting with cervical dystonia [6,7] . Several studies have attempted and failed in differentiating idiopathic cervical dystonia from posttraumatic cervical dystonia [9,10] .…”
Section: Dear Editor mentioning
confidence: 51%
See 1 more Smart Citation
“…The authors found that the corticospinal tracts demonstrated dysfunction in all patients, while SSEPs remained normal [8] . The theory of corticospinal tract dysfunction or other long tract dysfunction, such a spinothalamic tract, is further supported by the case reports on cervical intramedullary tumors presenting with cervical dystonia [6,7] . Several studies have attempted and failed in differentiating idiopathic cervical dystonia from posttraumatic cervical dystonia [9,10] .…”
Section: Dear Editor mentioning
confidence: 51%
“…We would like to offer an additional case and a few comments on the pathophysiology of cervical dystonia and its relationship to postoperative cervical spine surgery. First, postoperative cervical spine dystonia has been reported in numerous cases [3][4][5][6][7] . Cappelle et al [3] presented 6 patients that developed movement disorders associated with persistent dermatomal or segmental pain after spinal surgery and the anatomic distribution of the movement disorder was related to the nerve or spinal segment of the corresponding level of surgery.…”
Section: Dear Editor mentioning
confidence: 99%
“…This explanation was therefore invalid for our case. Cammarato et al . (1995) described a case with cervical dystonia that was improved after removal of the cervical spinal cord epandymoma.…”
Section: Discussionmentioning
confidence: 89%
“…Other cases of secondary torticollis have been related to intramedullary spinal cord disease such as ependymoma, glioma, and inflammatory demyelination. [3][4][5][6][7] Some of these resolved with removal of the spinal tumor. One case of athetosis-dystonia has been reported secondary to an intramedullary tumor, but the outcome was not stated.…”
Section: Discussionmentioning
confidence: 99%